2021
DOI: 10.1186/s12992-021-00756-7
|View full text |Cite
|
Sign up to set email alerts
|

A chair at the table: a scoping review of the participation of refugees in community-based participatory research in healthcare

Abstract: Background Refugees often face psychosocial complexity and multi-dimensional healthcare needs. Community-Based Participatory Research (CBPR) methods have been previously employed in designing health programs for refugee communities and in building strong research partnerships in refugee communities. However, the extent to which these communities are involved remains unknown. Objective To review the evidence on the involvement of refugees in CBPR pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…As the needs of refugee communities are so diverse, efforts should be made to include refugees as partners in all stages of the research process. In a scoping review of refugee participation in the CBPR, researchers reported refugees having less involvement in data analysis, knowledge translation/dissemination, the inception of the research study, obtaining funding, or contributing to scale up initiatives (Filler et al, 2021 ). Building strong partnerships should also include working with refugees from diverse backgrounds and community members at different stages of the post-resettlement phase (from newly resettled to former refugees).…”
Section: Discussionmentioning
confidence: 99%
“…As the needs of refugee communities are so diverse, efforts should be made to include refugees as partners in all stages of the research process. In a scoping review of refugee participation in the CBPR, researchers reported refugees having less involvement in data analysis, knowledge translation/dissemination, the inception of the research study, obtaining funding, or contributing to scale up initiatives (Filler et al, 2021 ). Building strong partnerships should also include working with refugees from diverse backgrounds and community members at different stages of the post-resettlement phase (from newly resettled to former refugees).…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest keeping the same contributors involved over longer periods of time as their trust is likely to increase, and their input improve, over time. A key problem is that projects are limited in time, and so is funding for PPI (Filler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Refugee involvement in research is one example of involving public contributors from a seldom-heard group (Doná, 2007 ; Filler et al, 2021 ; Gaywood et al, 2020 ; Strokosch & Osborne, 2016 ). In a recent review by Filler et al ( 2021 ), several published examples of refugee involvement in health research were presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges underscore the need to promote upstream structural changes to improve health outcomes in a participatory framework. This participatory approach, particularly with refugee communities, has been inconsistently applied to date ( Filler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%